Bidirectional Impact of Varying Severity of Acute Kidney Injury on Calcium Oxalate Stone Formation - Yu Yang; Junkai Huang; Xiaochen Ma; Haijie Xie; Linguo Xie; Chunyu Liu (Karger Publishers, 2024)
Introduction: Acute kidney injury (AKI) is a prevalent renal disorder. The occurrence of AKI may promote the formation of renal calcium oxalate stones by exerting continuous effects on renal tubular epithelial cells (TECs). We aimed to delineate the molecular interplay between AKI and nephrolithiasis. Methods: A mild (20 min) and severe (30 min) renal ischemia-reperfusion injury model was established in mice. Seven days after injury, calcium oxalate stones were induced using glyoxylate (Gly) to evaluate the impact of AKI on the formation of kidney stones. Transcriptome sequencing was performed on TECs to elucidate the relationship between AKI severity and kidney stones. Key transcription factors (TFs) regulating differential gene transcription levels were identified using motif analysis, and pioglitazone, ginkgetin, and fludarabine were used for targeted therapy to validate key TFs as potential targets for kidney stone treatment. Results: Severe AKI led to increased deposition of calcium oxalate crystals in renal, impaired kidney function, and upregulation of kidney stone-related gene expression. In contrast, mild AKI was associated with decreased crystal deposition, preserved kidney function, and downregulation of similar gene expression. Transcriptomic analysis revealed that genes associated with inflammation and cell adhesion pathways were significantly upregulated after severe AKI, while genes related to energy metabolism pathways were significantly upregulated after mild AKI. An integrative bioinformatic analysis uncovered a TF regulatory network within TECs, pinpointing that PKNOX1 was involved in the upregulation of inflammation-related genes after severe AKI, and inhibiting PKNOX1 function with pioglitazone could simultaneously reduce the increase of calcium oxalate crystals after severe AKI in kidney. On the other hand, motif analysis also revealed the protective role of STAT1 in the kidneys after mild AKI, enhancing the function of STAT1 with ginkgetin could reduce kidney stone formation, while the specific inhibitor of STAT1, fludarabine, could eliminate the therapeutic effects of mild AKI on kidney stones. Conclusion: Inadequate repair of TECs after severe AKI increases the risk of kidney stone formation, with the upregulation of inflammation-related genes regulated by PKNOX1 playing a role in this process. Inhibiting PKNOX1 function can reduce kidney stone formation. Conversely, after mild AKI, effective cell repair through upregulation of STAT1 expression can protect TEC function and reduce stone formation, and activating STAT1 function can also achieve the goal of treating kidney stones.